2021
DOI: 10.1371/journal.pone.0251527
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in cystic fibrosis: A multicentre prospective study with a control group, Italy, February-July 2020

Abstract: Objective To describe the symptoms and clinical course of SARS-CoV-2 infection in patients with cystic fibrosis (CF). Methods We carried out a prospective multicentre cohort study based on 32 CF centres and 6597 patients. Centres were contacted to collect baseline and follow-up data of patients who reported symptoms suggestive of COVID-19 or who had contact with a positive/suspected case between the end of February and July 2020. Symptoms and clinical course of the infection were compared between patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 16 publications
2
38
0
4
Order By: Relevance
“…In Colombo’s study, organ transplantation status and need for oxygen therapy before SARS-CoV-2 infection has been identified as the major risk factors for hospitalization ( 11 ). The prognostic role of organ transplantation, partially explained by the use for immunosuppressants, had also been described in earlier studies, in which organ recipients were found to have higher hospitalization rates, need for ICU and risk of death ( 6 , 7 , 14 ).…”
Section: Discussionsupporting
confidence: 53%
“…In Colombo’s study, organ transplantation status and need for oxygen therapy before SARS-CoV-2 infection has been identified as the major risk factors for hospitalization ( 11 ). The prognostic role of organ transplantation, partially explained by the use for immunosuppressants, had also been described in earlier studies, in which organ recipients were found to have higher hospitalization rates, need for ICU and risk of death ( 6 , 7 , 14 ).…”
Section: Discussionsupporting
confidence: 53%
“…As previously reported for the first pandemic wave [ 20 ], CF patients infected by SARS-CoV-2 presented unspecific symptoms, which could have been easily mistaken for a typical pulmonary exacerbation. However, for a non-negligible share of the symptomatic population (∼15%), they lasted more than one month.…”
Section: Discussionmentioning
confidence: 76%
“…However, for a non-negligible share of the symptomatic population (∼15%), they lasted more than one month. In addition, during the first wave of the pandemic, most COVID-19 cases were reported in Northern Italy [ 20 ], while during the subsequent waves, all the Italian centers involved in this study documented COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the clinical course of COVID-19 in this population show that most infected patients fully recovered without shortterm sequalae, although COVID-19 can be a serious illness in those with severe lung disease and organ transplantation [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 90%